Membangun Wirausaha dan Kemandirian Anak-Anak Panti Asuhan Al Ihsan Melalui Pelatihan Pembuatan Selai Tomat - Rahmi Awalina; Reni Koja; Nika Rahma Yanti; Wellyalina Wellyalina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
The ideal entrepreneur figure requires human qualities that can be competitive. Upgrading humans into functional beings is insufficient to provide intelligence, skills or technical expertise. The primary priority needed is to build a good mental attitude. The training activity for making tomato jam is an opportunity for the orphanage children to increase their knowledge with the hope that their abilities and knowledge will develop and be applied in their lives. The motivation given to the training activities made the children feel that being a child in an orphanage was not an obstacle to continuing to develop. This service activity aims to educate orphanage children with training in making tomato jam as a provision for entrepreneurship. This community service activity was carried out in two stages, including lectures for delivering material and demonstrations of making tomato jam by the service team for orphanage children. The participants of this activity were 25 girls from the Al Ihsan Orphanage in Padang, West Sumatra. Based on the results of the questionnaire that the training participants filled out after the activity, showed that the orphanage children understood every process and practice in making tomato jam well.